Severe acute respiratory syndrome corona virus-2 among children in India: can the risk of outbreak be prevented during the subsequent waves of COVID-19 pandemic? - Rao, Rajath; Pati, Binod Kumar; Kanungo, Srikanta; Nirala, Santosh Kumar; Naik, Bijaya Nanda (International Journal of Contemporary Pediatrics, 2021)
The COVID-19 pandemic believed to be originated from Wuhan, China has devastated the health and wealth of the entire world with multiple waves. An age shifting phenomenon towards younger age has been observed with SARS-CoV-2 (severe acute respiratory syndrome corona virus-2) with subsequent waves across the world including India. With vaccination being already in place for adults and elderly, younger especially children less than 18 years may be assumed to be susceptible to SARS-CoV-2 in the subsequent waves. However, few research suggests that children are less susceptible to SARS-CoV-2 due to immature sinuses in the nasopharynx and less number of ACE-2 receptors to which generally the SARS-CoV-2 attaches. On the other hand, poor health and nutrition status of the children, unreached target of immunization services, poor sanitation and fragile health system in India makes children more vulnerable to SARS-CoV-2. Children may get affected if new variant of virus emerges during the subsequent waves. So, we need to prepare to protect the children who if at all get affected during the third wave of COVID-19 by preventing infection among adult and elderly, strengthening the health system and immunizing the children.